Patterns of use of wild food plants by Brazilian local communities: systematic review and meta-analysis - Lailson César Andrade Gomes; Patrícia Muniz de Medeiros; Ana Paula do Nascimento Prata (Journal of Ethnobiology and Ethnomedicine, 2023)
Abstract Background This systematic review and meta-analysis sought to investigate the patterns of use of native wild food plants of Brazil (native and non-cultivated). Methods We searched ethnobiological works with food plants in Web of Science, Scielo, Scopus and PubMed using different sets of keywords. Initially, the studies were evaluated based on inclusion criteria (systematic data collection instruments, such as interviews; specification of methods for data collection; and the presence of a species list). The methodological quality of each study was evaluated to define the risk of bias. A total of 20 articles met all criteria and were included in the review. Results The results showed that there was a predominance of consumption of fruits, followed by leaves and seeds, which together represented 85.8% of the total parts. As for the meta-analysis, there was a predominance of use of plant parts classified as reproductive, non-persistent, non-destructive and parts of woody plants. There was no interference from the type of ecosystem (seasonally dry x moist). The results did not support the seasonality hypothesis. Conclusions The concentration of studies in the Northeast, Southeast and South regions of Brazil and in the Atlantic Forest and Caatinga biomes points to the need for a greater effort in terms of quantitative ethnobotanical research in other regions and biomes. The predominance of fruits and plant parts classified as reproductive, non-persistent and non-destructive points to the high potential for implementation of sustainable management strategies aimed at these plants in the country.